Ruptured Giant Omphalocele. A Case Report - Víctor Manuel González Valdez; Martha Ofarrill Sánchez; Yaquelín González Ricardo (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2013)
Omphalocele is one of the abdominal wall defects. It can be associated with other malformations including imperforate anus, agenesis of the colon, bladder exstrophy and cardiovascular disease, frequently leading to non-viable fetuses. A case of a female newborn who was prematurely delivered (35.3 weeks) in Belize with low birth weight (1860 g) is presented. This first-born child required emergency surgery at ten hours of life for ruptured giant omphalocele associated with tetralogy of Fallot, hypoglycemia, and severe general malaise. The aim of this report is to present the diagnostic and therapeutic procedures in such cases. Given the appropriate prenatal diagnosis implemented in Cuba, it is unusual for Cuban doctors, except those working abroad, to treat these patients; hence, this paper may be useful in the teaching context.